Implementasi Agile dalam Perancangan UI/UX Sistem Informasi Absensi Siswa di MTS Muhammadiyah 01 Medan - Ali Ikhwan; Asri Akmaliyah Syahfitri; Vidya Ramadhani; Muhammad Yusuf Siregar; Zikri Ezza Alhira (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The implementation of the Agile method in designing the UI/UX for the student attendance information system at MTS Muhammadiyah 01 Medan resulted in a responsive, efficient, and user-friendly interface design. The Agile approach allowed for iterative and adaptive design development, utilizing user feedback for refinement at each stage. The design process included requirements gathering, design, testing, and evaluation with a focus on user experience. The resulting UI/UX design makes it easier for teachers to manage attendance, replacing the inefficient and error-prone manual methods. This implementation also supports the digitalization of administrative processes in the educational environment, improving accessibility, efficiency, and user comfort. With an intuitive design that meets user needs, this system is expected to be widely adopted, having a positive impact on data management in schools, and serving as a model for similar development in the future.